Initial reliability assessment of a commercial-off-the-shelf GPS sensor for generic UAVs - Thanaraj, T. (2022)
Unmanned aerial vehicles (UAVs) have gathered much attention commercially in recent times owing to the advancement in technology, such as the introduction of brushless-DC motors and micro-electromechanical systems (MEMS). As a result, these UAVs can undertake complex missions and pose potential benefits to a multitude of use cases, for instance, last-mile cargo delivery, infrastructure inspection, and even search-and-rescue missions. With the increase in the adoption of UAVs and the abundance of commercial-off-the-shelf (COTS) components, the airworthiness of the UAVs grows to be of concern as the assessment criteria for them are not as stringent as that of manned aircraft, largely due to the absence of an onboard pilot or passengers. In addition, UAVs with COTS components lack data to provide assurance of their reliability and determine if the UAVs are fit to fly. On-board navigational sensors are one of the critical subsystems in a UAV and any deterioration in the performance of these sensors can precipitate into a UAV system failure during flight missions, potentially leading to a crash. As such, the reliability of these sensors has to be ascertained before any flight mission to ensure their airworthiness. In this paper, we will assess a COTS GPS sensor that has been commonly used in self-assembled UAVs and predict its reliability based on the characteristics of the Surface Mounted Devices (SMD) and Integrated Circuits (IC) using MIL-HDBK-217F. Results from this assessment will provide a preliminary representation of the reliability of a typical COTS GPS sensor for the determination of its suitability for its intended operation.